2016
DOI: 10.1556/1646.8.2016.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cellular composition of periodontal pockets

Abstract: PurposeThe development of inflammatory periodontal disease in young people is an urgent problem of today's periodontology, and requires a development of new methods that would give an opportunity not only to diagnose but also for prognosis of periodontitis course in a given patients contingent.ResultsCellular structure of periodontal pockets is presented by hematogenous and epithelial cells. Our results are confirmed by previous studies, and show that the penetration of periodontal pathogens leads to formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
3
12
0
2
Order By: Relevance
“…Improved cytomorphometric indicators were observed among patients with periodontal diseases, depending on the material of prostheses. The results revealed improvement among the patients in the C/C-Zr group compared with the C group, which was also confirmed by several studies [ 20 , 22 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Improved cytomorphometric indicators were observed among patients with periodontal diseases, depending on the material of prostheses. The results revealed improvement among the patients in the C/C-Zr group compared with the C group, which was also confirmed by several studies [ 20 , 22 ].…”
Section: Discussionsupporting
confidence: 84%
“…Several studies have been conducted to determine the cytological composition of gingival crevicular fluid (GCF) in inflammatory diseases of periodontal tissues for diagnostic purposes [ 18 , 19 , 20 , 21 ]. However, there remain no comparative data on the change in GCF parameters during prosthodontic treatment using fixed prosthesis fabricated from various materials [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These provisions provide further development in the course and agree with the basic developments on the peculiarities of the cytological organization of gums in normal state and in inflammation [18][19]. Some differences are due to age-standardized aspect [20].…”
Section: Resultssupporting
confidence: 73%
“…The cellularity and degree of cellular changes are characterized by the pathological condition of periodontitis in the patient contingent. In a similar study by Hasiuk et al 23 observed that 15% of immature epithelial cells in the periodontal pockets of patients with generalized periodontics. Lesser number of superficial cells indicates the disturbed maturation of epithelial layers in the gingival mucosa because of inflammation and irritation from pathogens and other factors.…”
Section: Discussionmentioning
confidence: 78%